Mandibular reconstruction after cancer: an in-house approach to manufacturing cutting guides. Issue 1 (January 2017) - Bosc, R.; Hersant, B.; Carloni, R.; Niddam, J.; Bouhassira, J.; De Kermadec, H.; Bequignon, E.; Wojcik, T.; Julieron, M.; Meningaud, J.-P.
Abstract: The restoration of mandibular bone defects after cancer can be facilitated by computer-assisted preoperative planning. The aim of this study was to assess an in-house manufacturing approach to customized cutting guides for use in the reconstruction of the mandible with osteocutaneous free flaps. A retrospective cohort study was performed, involving 18 patients who underwent mandibular reconstruction with a fibula free flap at three institutions during the period July 2012 to March 2015. A single surgeon designed and manufactured fibula and mandible cutting guides using a computer-aided design process and three-dimensional (3D) printing technology. The oncological outcomes, production parameters, and quality of the reconstructions performed for each patient were recorded. Computed tomography scans were acquired after surgery, and these were compared with the preoperative 3D models. Eighteen consecutive patients with squamous cell carcinoma underwent surgery and then reconstruction using this customized in-house surgical approach. The lengths of the fibula bone segments and the angle measurements in the simulations were similar to those of the postoperative volume rendering ( P  = 0.61). The ease of access to 3D printing technology has enabled the computer-aided design and manufacturing of customized cutting guides for oral cancer treatment without the need for input from external laboratories.